Analisis Status Trofik Dan Struktur Saprobik Fitoplankton Di Bendungan Telaga Tunjung, Kabupaten Tabanan, Bali - I Gede Pransidi; Ni Made Darmadi; I Wayan Arya; Dewa Gede Semara Edi; I Made Kawan (GEMA AGRO, 2020)
Plankton is instrumental in the aquatic ecosystem, plankton can be an indicator of fertility and pollution. The quality of a water especially the flooded waters can be determined based on the fluctuations of the plankton population that will affect the trophic levels of the waters. The quality of a water can be measured by knowing the value of the Saprobic Index (SI). The Saprobic index is an index that closely relates to the pollution level. This research aims to determine the level of fertility and pollution levels in the waters of Telaga Tunjung Dam, based on the status of Trophic and Saprobic's structure of Phytoplankton, knowing the relationship (linkage) of trophic status and structure Saprobic phytoplankton with variable water quality in Telaga Tunjung Dam. The methods of study used are descriptive methods of case study. The research was conducted on five stations with four repetitions. Plankton sampling performed actively using plankton net with mesh size 60 Î¼m diameter 25 cm. Based on the results of the status of the trophic waters in Telaga Tunjung Dam is at the head of high Water Fertility (Eutrofik). The pollution level is mild to moderate water with a saprobic index from 0,739 to -0,583. The trophic level relationship and the saprobic structure with the water quality variable show that good water quality affects the abundance of high phytoplankton and mild to moderate pollution levels.